The Effect of Hospice on Hospital Admission and Readmission Rates: A Review. Issue 3 (August 2018) - Treece, Jennifer; Ghouse, Mustafa; Rashid, Saima; Arikapudi, Sowminya; Sankhyan, Pratyaksha; Kohli, Varun; O'Neill, Luke; Addo-Yobo, Emmanuel; Bhattad, Venugopal; Baumrucker, Steven J.
Symptom control may become challenging for terminally ill patients as they near the end of life. Patients often seek hospital admission to address symptoms, such as pain, nausea, vomiting, and restlessness. Alternatively, palliative medicine focuses on the control and mitigation of symptoms, while allowing patients to maintain their quality of life, whether in an outpatient or inpatient setting. Hospice care provides, in addition to inpatient care at a hospice facility or in a hospital, the option for patients to receive symptom management at home. This option for symptom control in the outpatient setting is essential to preventing repeated and expensive hospital readmissions. This article discusses the impact of hospice care on hospital readmission rates.